Β-galactosidase GALA from Bacillus circulans with high transgalactosylation activity. Issue 1 (1st January 2021) - Yan, Yaru; Guan, Weishi; Li, Xiaoyi; Gao, Kaier; Xu, Xinxin; Liu, Bo; Zhang, Wei; Zhang, Yuhong
ABSTRACT: β-galactosidase catalyzes lactose hydrolysis and transfers reactions to produce prebiotics such as galacto-oligosaccharides (GOS) with potential applications in the food industry and pharmaceuticals. However, there is still a need for improved transgalactosylation activity of β-galactosidases and reaction conditions of GOS production in order to maximize GOS output and reduce production costs. In this study, a β-galactosidase gene, galA, from Bacillus circulans was expressed in Pichia pastoris, which not only hydrolyzed lactose but also had strong transgalactosylation activity to produce GOS. Response surface methodology was adopted to investigate the effects of temperature, enzyme concentration, pH, initial lactose concentration, and reaction time on the production of GOS and optimize the reaction conditions for GOS. The optimal pH for the enzyme was 6.0 and remained stable under neutral and basic conditions. Meanwhile, GALA showed most activity at 50°C and retained considerable activity at a lower temperature 30–40°C, indicating this enzyme could work under mild conditions. The enzyme concentration and temperature were found to be the critical parameters affecting the transgalactosylation activity. Response surface methodology showed that the optimal enzyme concentration, initial lactose concentration, temperature, pH, and reaction time were 3.03 U/mL, 500 g/L, 30°C, 5.08, and 4 h, respectively. Under such conditions, the maximum yield of GOS was 252.8 g/L, accounting for approximately 50.56% of the total sugar. This yield can be considered relatively high compared to those obtained from other sources of β-galactosidases, implying a great potential for GALA in the industrial production and application of GOS.